Fermentation of cereal, pseudo-cereal and legume materials with Propionibacterium freudenreichii and Levilactobacillus brevis for vitamin B12 fortification. (February 2021) - Xie, Chong; Coda, Rossana; Chamlagain, Bhawani; Edelmann, Minnamari; Varmanen, Pekka; Piironen, Vieno; Katina, Kati
Abstract: The present study investigated the in situ production of vitamin B12 in eleven cereal, pseudo-cereal and legume materials by fermentation with Propionibacterium freudenreichii DSM 20271 and Levilactobacillus brevis (formerly Lactobacillus brevis ) ATCC 14869. P. freudenreichii was used as the vitamin producer and L. brevis was selected to improve the consistency and microbial safety of the process. The study showed that more than 300 ng/g dw of vitamin B12 (daily requirement: 2.4 μg) were produced during fermentation in most of the studied brans and legumes. The highest vitamin B12 production was observed in the fermentation of the rice bran (ca. 742 ng/g dw), followed by the fermentation of buckwheat bran (ca. 631 ng/g dw). Furthermore, partial least squares (PLS) regression analysis suggested that the production of vitamin B12 was greatly influenced by the nutrient composition of the fermented raw materials. Meanwhile, L. brevis was found to effectively inhibit the growth of Enterobacteriaceae during fermentation. These results demonstrated that fermentation of cereal, pseudo-cereal and legume materials with P. freudenreichii and L. brevis is effective in fortifying plant-based food with vitamin B12. Highlights: More than 300 ng/g of vitamin B12 was produced in various materials. The highest vitamin B12 production was found in the rice bran fermentation. Nutrient composition of materials significantly influenced vitamin B12 production. L. brevis can inhibit the growth of Enterobacteriaceae during fermentation.